Biased competition between Lgr5 intestinal stem cells driven by oncogenic mutation induces clonal expansion. (16th December 2013) - Snippert, Hugo J.; Schepers, Arnout G.; van, Johan H.; Simons, Benjamin D.; Clevers, Hans
Abstract The concept of 'field cancerization' describes the clonal expansion of genetically altered, but morphologically normal cells that predisposes a tissue to cancer development. Here, we demonstrate that biased stem cell competition in the mouse small intestine can initiate the expansion of such clones. We quantitatively analyze how the activation of oncogenic K‐ras in individual Lgr5+ stem cells accelerates their cell division rate and creates a biased drift towards crypt clonality. K‐ras mutant crypts then clonally expand within the epithelium through enhanced crypt fission, which distributes the existing Paneth cell niche over the two new crypts. Thus, an unequal competition between wild‐type and mutant intestinal stem cells initiates a biased drift that leads to the clonal expansion of crypts carrying oncogenic mutations.